2007
DOI: 10.1016/j.juro.2007.08.049
|View full text |Cite
|
Sign up to set email alerts
|

Climatic Conditions and the Risk of Testicular Torsion in Adolescent Males

Abstract: An increased incidence of testicular torsion is seen with decreasing atmospheric temperature and humidity, suggesting a possible etiological role.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
42
1
3

Year Published

2009
2009
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(54 citation statements)
references
References 9 publications
6
42
1
3
Order By: Relevance
“…Testicular torsion is a urological syndrome caused mainly by a twist in the spermatic cord has been implicated in testicular injury and infertility (Williamson 1977). Testicular torsion has a prevalence of approximately 1 case per 125 males (Srinivasan et al 2007). This syndrome often leads to infertility of the ipsilateral (IL) (torted) and contralateral (CL) (not torted) testis, an outcome that makes surgical intervention mandatory (Filho et al 2004).…”
Section: Tohoku University Medical Pressmentioning
confidence: 99%
“…Testicular torsion is a urological syndrome caused mainly by a twist in the spermatic cord has been implicated in testicular injury and infertility (Williamson 1977). Testicular torsion has a prevalence of approximately 1 case per 125 males (Srinivasan et al 2007). This syndrome often leads to infertility of the ipsilateral (IL) (torted) and contralateral (CL) (not torted) testis, an outcome that makes surgical intervention mandatory (Filho et al 2004).…”
Section: Tohoku University Medical Pressmentioning
confidence: 99%
“…patients evaluated (3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15). Different conclusions were drawn from these studies regarding the validity of the hyperactive cremasteric reflex theory.…”
Section: Introductionmentioning
confidence: 99%
“…of testicular damage following the torsion and detorsion processes (Lysiak et al, 2000;Nadiri et al, 2006;Srinivasan et al, 2007;Minutoli et al, 2009Minutoli et al, , 2012, which have been considered similar to ischemia-reperfusion injuries observed in different organs (Eltzschig and Eckle, 2011).…”
Section: Role Of Nlrp3 Inflammasome In Testicular Ischemiamentioning
confidence: 75%
“…This pathologic cascade is responsible for the testicular atrophy and impaired spermatogenesis observed at a later stage (Filho et al, 2004;Antonuccio et al, 2006;Nadiri et al, 2006;Srinivasan et al, 2007;Minutoli et al, 2009Minutoli et al, , 2012. Even if the importance of early events is well recognized, the late phase of TI/R is crucial from a clinical point of view as the testis morphology and function could be severely impaired (Altavilla et al, 2012;Cvetkovic et al, 2015).…”
Section: Role Of Nlrp3 Inflammasome In Testicular Ischemiamentioning
confidence: 99%